Childhood adrenocortical carcinoma as a sentinel cancer for detecting families with germline TP53 mutations - Choong, S.S.; Latiff, Z.A.; Mohamed, M.; Lim, L.L.W.; Chen, K.S.; Vengidasan, L.; Razali, H.; Abdul Rahman, E.J.; Ariffin, H. (Wiley, 2012)
Li-Fraumeni syndrome (LFS) is a highly penetrant, autosomal dominant disorder where affected individuals carry a 50% risk of developing cancer before 30 years of age. It is most commonly associated with mutations in the tumour suppressor gene, TP53. Adrenocortical carcinoma (ACC) is a very rare paediatric cancer, and up to 80% of affected children are found to carry germline TP53 mutations. Hence, we propose using childhood ACC incidence as selection criteria for referral for TP53 mutation testing, independent of familial cancer history. Under the auspices of the Malaysian Society of Paediatric Haematology–Oncology, four eligible children diagnosed with ACC over a 30-month study period were referred for mutation testing. Three had a germline TP53 mutation. Subsequent TP53 testing in relatives showed two inherited mutations and one de novo mutation. These findings strongly support paediatric ACC as a useful sentinel cancer for initiating a germline TP53 /LFS detection programme, particularly in countries where the lack of structured oncogenetic practice precludes the identification of families with LFS features.